Efluente de curtume causa danos biométricos, comportamentais e mutagênicos em tilápia-do-Nilo (Oreochromis niloticus) - Teodoro, Diêgo Alberto; Paixão, Caroliny Fátima Chaves da; Araújo, Amanda Pereira da Costa; Cardoso, Marcelo Vieira; Chagas, Thales Quintão; Castro, André Luis da Silva (Multi-Science Journal, 2017)
não há